Pengaruh Penguasaan Kosa Kata Terhadap Kemampuan Pemahaman Teks Buku IPA Pada Mahasiswa Program Studi PGSD FKIP Uncen Tahun 2025 - Kaigere, Daud; Ayomi, Golden Ringgo SC. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of vocabulary mastery on the ability to comprehend Science (IPA) textbook texts among students of the Primary School Teacher Education Program, Faculty of Teacher Training and Education, Universitas Cenderawasih, in 2025. Academic and scientific vocabulary mastery is considered a crucial factor in supporting students’ reading literacy, especially in understanding science texts that contain conceptual terminology and complex scientific language structures. This research employed a quantitative approach with a correlational design. The sample consisted of 60 Primary School Teacher Education Program students selected through purposive sampling. Data were collected using a scientific vocabulary mastery test and a science text comprehension test. Data analysis was conducted using Pearson correlation and simple regression. The results revealed a strong positive relationship between vocabulary mastery and science text comprehension, with a correlation coefficient of r = 0.72 (p < 0.01). Furthermore, vocabulary mastery contributed 52% to the variance in students’ text comprehension ability (R² = 0.52). These findings indicate that higher vocabulary mastery leads to better comprehension of science textbook texts. Therefore, this study highlights the importance of strengthening scientific vocabulary as an effective strategy to improve science literacy among prospective elementary school teachers.